Effects of early weaning on carcass and ribeye steak characteristics of bulls and steers - Schlickau, E.K.; Dikeman, Michael E.; Marston, T.T.; Brethour, J.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred Hereford × Angus calves (n = 103) were used to determine the effect of early weaning on carcass and ribeye (longissimus muscle) characteristics of bulls and steers. Treatments were: 1) early-weaned (117 days of age) bulls, 2) early-weaned steers, 3) normal-weaned (220 days of age) bulls, and 4) normal-weaned steers. Cattle were harvested at 360 and 389 days of age. At 36 hours postmortem, carcass quality and cutability were measured. Ribeye steaks were aged 14 days and scored for color, Warner-Bratzler shear force, and sensory panel evaluations. Carcasses from early-weaned cattle had greater dressing percentages, heavier weights, greater fat thicknesses, and higher numerical USDA Yield Grades (lower cutability). They also had more marbling and greater USDA quality grades, but had similar longissimus color, shear force, and sensory panel scores, compared with those of normal-weaned cattle. Bulls had greater dressing percentages, but had similar carcass weights to steers. Bull carcasses had less fat thickness and greater ribeye areas, resulting in lower numerical USDA Yield Grades (higher cutability) than steers had. They also had less marbling, darker color, and lower USDA quality grades than steers did. Longissimus muscles from bulls were darker, had greater shear forces, and had lower sensory panel tenderness scores than those from steers. For early-maturing British-type cattle, early weaning is a viable management strategy to produce heavier, higher-quality carcasses than those of normal-weaned cattle. Carcasses from early-weaned cattle are fatter and have lower cutability. For a non-implant “natural” market, bulls could be an alternative for producing high-cutability carcasses. Steaks may be less tender, however, and pre-harvest management must be optimized to reduce dark-cutting carcasses.
Keywords: Beef; Early weaning; Carcass; Ribeye steak